Многоязычие в Карелии - Laine, Alina (Humboldt-Universität zu Berlin, 2024)
На основании данных, собранных в Республике Карелия и Тверской области, анализируются социо-лингвистические факторы, определяющие использо-вание языков разными поколениями этнических карел. Итоги обследования помогают получить более полное представление о динамике использования карельского языка родившимися в разные исторические периоды, а также выявить факторы, которые способствуют или препятствуют его сохранению и развитию. Based on data collected in the Republic of Karelia and the Tver Oblast, this study analyzes sociolinguistic factors in-fluencing the use of languages among different generations of ethnic Karelians. The findings of the survey help to gain a more comprehensive understanding of the dynamics of Karelian language usage among individuals born in various historical periods and identify factors that facilitate or hin-der its preservation and development.